Productivity and economic viability of winter niger [Guizotia abyssinica (L.f.) Cass.] under varying nutrient management practices: PRODUCTIVITY AND ECONOMIC VIABILITY OF NIGER UNDER NUTRIENT MANAGEMENT PRACTICES - M R DESHMUKH; ALOK JYOTISHI; A R G RANGANATHA (Journal of Oilseeds Research, 2015)
Results of the field experiments conducted in Vertisols of Jabalpur, Madhya Pradesh on irrigated niger (cv. JNC-1) during winter season for three consecutive years (2008-09 to 2010-11) revealed that application of 40 kg N + 30 kg P2O5 + 20 kg K2O/ha (recommended dose of fertilizer) along with spraying of 2% DAP twice at flowering and capitula formation stage showed higher seed (647 kg/ha); oil yield (198 kg/ha), and net monetary returns (` 7867/ha). This was at par with recommended dose of fertilizer (RDF) along with spraying of 2% urea twice. Application of 75% RDF along with spraying of 2% DAP twice at the same stage was comparable to 100% RDF alone with regard to productivity and economic viability. Numerically,spraying of DAP proved better than spraying of urea in respect of production and profit.